Molten Salt Reactor thermal-fluid dynamics evaluation using a CFD code for a theoretical power density distribution - Deiglys Borges Monteiro; Letícia Caroline Gonçalvez; José Rubens Maiorino; Pedro Carlos Russo Rossi (Brazilian Journal of Radiation Sciences)
The molten salt reactors are a kind of nuclear reactor that had received additional attention worldwide due to their inherent safety features and the possibility of use the Thorium, a more abundant resource than Uranium, as a fuel. Despite of this promise concept and works being developed or under course, some aspects related to their thermal hydraulics should be better understand. In this work, the initial thermal-hydraulics results obtained using the ANSYS-CFXÒ code are presented. The simulations were conducted in 3D for 1/16 of a cylinder volume that represents the molten reactor core. The results show a good agreement for this simplified geometry and for a theoretical power density distribution between the benchmark work and those obtained within this for the temperature. An evaluation for the other properties and for different turbulence models, among others, are planned for future.